1994
DOI: 10.1002/bip.360340504
|View full text |Cite
|
Sign up to set email alerts
|

Nmr and molecular modeling investigations of the neuropeptide bradykinin in three different solvent systems: DMSO, 9 : 1 dioxane/water, and in the presence of 7.4 mM lyso phosphatidylcholine micelles

Abstract: The linear nonapeptide hormone bradykinin (Arg1-Pro2-Pro3-Gly4-Phe5-Ser6-Pro7-Phe8-Arg9) is involved, either directly or indirectly, in a wide variety of physiological processes, particularly pain and hyperanalgesia. Additional evidence suggests that bradykinin also plays a major role in inflammatory response, asthma, sepsis, and symptoms associated with the rhinoviral infection. It has long been speculated that a beta-turn at the C-terminus of bradykinin plays a major role in the biological activity of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
59
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 34 publications
7
59
0
Order By: Relevance
“…These results are in remarkably good agreement with a model of BK bound to the B2 receptor proposed by Kyle based on structural homology Table II and Table III modeling, molecular modeling, and systematic conformational searching methods of BK and the receptor (22). Two-dimensional NMR and molecular modeling of BK in various solvents and micelles have revealed that Ser 6 through Arg 9 adopt a ␤-turn-like structure when in a hydrophobic environment (23,24). The importance of this ␤-turn for receptor binding was exploited by substituting constraining amino acids that mimic a ␤-turn at position 8 and 9 in BK antagonists (Table I).…”
Section: Discussionsupporting
confidence: 86%
“…These results are in remarkably good agreement with a model of BK bound to the B2 receptor proposed by Kyle based on structural homology Table II and Table III modeling, molecular modeling, and systematic conformational searching methods of BK and the receptor (22). Two-dimensional NMR and molecular modeling of BK in various solvents and micelles have revealed that Ser 6 through Arg 9 adopt a ␤-turn-like structure when in a hydrophobic environment (23,24). The importance of this ␤-turn for receptor binding was exploited by substituting constraining amino acids that mimic a ␤-turn at position 8 and 9 in BK antagonists (Table I).…”
Section: Discussionsupporting
confidence: 86%
“…9–11 Despite the tremendous interest in this molecule, only a fraction of its structure is characterized in detail. Circular dichroism, 12 Raman spectroscopy, 13 nuclear magnetic resonance, 14 and molecular modeling studies reveal that the BK Ser 6 –Pro 7 –Phe 8 –Arg 9 residues favor a β-turn motif, 15 whereas the region Arg 1 –Phe 5 is apparently unstructured. This combination of ordered and disordered regions hinders a complete determination of the BK structure.…”
mentioning
confidence: 99%
“…Such a high degree of flexibility suggests that binding to the receptor implies the selection of a particular structure from among the number of slowly or rapidly interconverting ones in solution. As a matter of fact, enhancement of the b-turn-forming potential of bradykinin was observed in the presence of SDS micelles [16,24±27], apolar organic solvents [14,18,20,27] or aqueous phospholipids [13,22,26]; as a consequence of all these findings, bradykinin is currently believed to adopt a C-terminal b turn upon complexation with the receptor [28].In the present study, NMR data were collected for bradykinin in dimethylsulfoxide containing 1% water in the presence of calcium, in order to ascertain whether the conformational equilibria and structural heterogeneity are affected by a divalent metal ion that may act as a mediator in the process of conformational selection. The water/dimethylsulfoxide solvent was chosen because most biochemical functions occur away from bulk water but may involve active molecules that retain some water of hydration.…”
mentioning
confidence: 99%